2018
DOI: 10.1136/bmjopen-2017-018978
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical behaviour patterns and levels of depressive symptoms, anxiety and well-being in middle-aged adults: a cross-sectional study using isotemporal substitution models

Abstract: ObjectiveTo examine the compositional effects of physical behaviour on mental health.DesignCross-sectional study.SettingA population-representative random sample (Mitchelstown cohort) was recruited from a large primary care centre in Mitchelstown, County Cork, Ireland.ParticipantsIn total 3807 potential participants were selected from the practice list. Following exclusion of duplicates, deaths and ineligibles, 3043 were invited to participate and of these, 2047 (49.2% men) completed the questionnaire and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 51 publications
(37 reference statements)
3
27
3
Order By: Relevance
“…of the accelerometer and other activities constant) was significantly associated with a decrease in anxiety symptoms [72]. However, these findings were not supported in the present analyses of walking where anxiety symptoms and status did not differ across groups.…”
Section: Walkingcontrasting
confidence: 93%
“…of the accelerometer and other activities constant) was significantly associated with a decrease in anxiety symptoms [72]. However, these findings were not supported in the present analyses of walking where anxiety symptoms and status did not differ across groups.…”
Section: Walkingcontrasting
confidence: 93%
“…To our knowledge only one small population based study [40] has previously employed the gold standard thigh worn position to examine sitting time in relation to depression. Our findings on device measured MVPA with both depression symptoms and diagnosis, supports the results from some previous studies [15,41], although others have only observed protective associations with light intensity activity and not MVPA [36][37][38][39]. It is conceivable that in older populations lighter intensity activity may be more beneficial for mental health as greater exertion during vigorous forms of exercise may produce discomfort and shortness of breath, thus feel less enjoyable.…”
Section: Comparison To Existing Literaturesupporting
confidence: 89%
“…Those that have were mostly conducted on small (n < 500) convenience samples. Most of these studies [35][36][37][38][39][40], but not all [15] have noted associations between device measured sitting and higher risk of depressive symptoms assessed from self-reported questionnaires.…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…Similarly, on the psychological level, there is ample evidence that regular physical activity is related to less subjective stress (e.g., Nguyen-Michel, Unger, Hamilton, & Spruijt-Metz, 2006), as well as less anxiety and depression (e.g., Harvey et al, 2017;McMahon et al, 2017;Penedo & Dahn, 2005;Rebar, Duncan, Short, & Vandelanotte, 2014;Stults-Kolehmainen & Sinha, 2014). Surprisingly, although intervention studies in both patients and nonclinical populations corroborate these beneficial effects of physical activity on stress and well-being (e.g., Dillon, McMahon, O'Regan, & Perry, 2018;Hiles, Lamers, Milaneschi, & Penninx, 2017;Rosenbaum, Tiedemann, & Ward, 2014;Stubbs et al, 2017), much uncertainty still exists on the specific mechanisms that underpin this relationship. One hypothesis holds that physical activity increases well-being through better coping with stressful encounters, which may include generally improved stressor appraisal or even specific styles of coping when faced with critical situations (e.g., Salmon, 2001;Sothmann, 2006;Steptoe, Kimbell, & Basford, 1998; also see Stults-Kolehmainen & Sinha, 2014).…”
Section: Physical Activity and Stress Adaptabilitymentioning
confidence: 99%